The Efficacy and Safety of Early Renal Replacement Therapy in Critically Ill Patients With Acute Kidney Injury: A Meta-Analysis With Trial Sequential Analysis of Randomized Controlled Trials - Xiao, Chuan; Xiao, Jingjing; Cheng, Yumei; Li, Qing; Li, Wei; He, Tianhui; Li, Shuwen; Gao, Daixiu; Shen, Feng (Frontiers in Medicine, 2022)
Background：Efficacy and safety of early renal replacement therapy (eRRT) for critically ill patients with acute kidney injury (AKI) remains controversial. Therefore, the purpose of our study is to perform a up-to-date meta-analysis with trial sequential analysis (TSA) of randomized-controlled trials (RCTs) to evaluate the therapeutic effect of eRRT on patients in ICU. Methods: We extensively searched MEDLINE, EMBASE, LILACS, the Cochrane Central Register of Controlled Trials and ClinicalTrials.gov, Grey Literature Report and BASE, and conducted an updated search on December 27, 2021.The included studies were RCTs which compared the efficacy and safety of early and delayed RRT (dRRT) on critically ill patients with AKI. We adopted TSA and Sensitivity analysis to strengthen the robustness of the results. Results: Twelve RCTs with a total of 5423 participants was included. Patients receiving eRRT and dRRT had similar all cause-mortality rate at day 28 (38.7% vs 38.9%) [risk ratio (RR), 1.00; 95% confidence interval (CI), 0.93 to 1.07, p = 0.93, I2 = 0%, p = 0.93]. Sensitivity and subgroup analysis produced similar results for the primary outcome. TSA showed the required information size was 5034, and the cumulative Z-curve crossed trial sequential monitoring boundaries for futility. Patients receiving eRRT had a higher rate of RRT (RR,1.50, 95%CI, 1.28 to 1.76, p<0.00001 , I2 = 96%), and experienced more adverse events comparing to those receiving dRRT (RR:1.41, 95% CI:1.22 to 1.63, p < 0.0001, heterogeneity not applied ). Conclusions: eRRT does not show any obvious beneficial effect on mortality for ill patients with AKI compared with dRRT and TSA indicated no more studies were needed to confirm it. eRRT tends to increase the rate of RRT and the risk of total adverse events.